An Earth‐Abundant Catalyst‐Based Seawater Photoelectrolysis System with 17.9% Solar‐to‐Hydrogen Efficiency. Issue 18 (22nd March 2018) - Hsu, Shao‐Hui; Miao, Jianwei; Zhang, Liping; Gao, Jiajian; Wang, Hongming; Tao, Huabing; Hung, Sung‐Fu; Vasileff, Anthony; Qiao, Shi Zhang; Liu, Bin
Abstract: The implementation of water splitting systems, powered by sustainable energy resources, appears to be an attractive strategy for producing high‐purity H2 in the absence of the release of carbon dioxide (CO2 ). However, the high cost, impractical operating conditions, and unsatisfactory efficiency and stability of conventional methods restrain their large‐scale development. Seawater covers 70% of the Earth's surface and is one of the most abundant natural resources on the planet. New research is looking into the possibility of using seawater to produce hydrogen through electrolysis and will provide remarkable insight into sustainable H2 production, if successful. Here, guided by density functional theory (DFT) calculations to predict the selectivity of gas‐evolving catalysts, a seawater‐splitting device equipped with affordable state‐of‐the‐art electrocatalysts composed of earth‐abundant elements (Fe, Co, Ni, and Mo) is demonstrated. This device shows excellent durability and specific selectivity toward the oxygen evolution reaction in seawater with near 100% Faradaic efficiency for the production of H2 and O2 . Powered by a single commercial III–V triple‐junction photovoltaic cell, the integrated system achieves spontaneous and efficient generation of high‐purity H2 and O2 from seawater at neutral pH with a remarkable 17.9% solar‐to‐hydrogen efficiency. Abstract : A seawater photoelectrolysis system based on earth‐abundant catalysts is developed, which exhibits excellent durability and specific selectivity toward the oxygen evolution reaction with a remarkable 17.9% solar‐to‐hydrogen conversion efficiency.